Agricultural credit provision: what really determines farmers' participation and credit rationing?. Issue 2 (3rd July 2017) - Asante-Addo, Collins; Mockshell, Jonathan; Zeller, Manfred; Siddig, Khalid; Egyir, Irene S.
Abstract : Purpose: The purpose of this paper is to analyze determinants of farmers' participation and credit rationing in microcredit programs using survey data from Ghana. Design/methodology/approach: The authors use the Garrett Ranking Technique to analyze farmers' reasons for participation or non-participation in credit programs, a probit regression model to estimate factors influencing farm households' participation, and the Heckman's sample selection model to identify factors influencing farm households' probability of being credit rationed by microcredit programs. Findings: The results reveal that farm households participate in credit programs because of improved access to savings services and agricultural loans. Fear of loan default and lack of savings are reasons for non-participation in credit programs. Furthermore, membership in farmer-based organizations (FBOs) and the household head's formal education are positively associated with farmers' participation in credit programs. The likelihood of farmers being credit rationed (i.e. their loan applications were either rejected or the amount of credit they applied for was reduced) is less likely among higher income farmers and members of FBOs such as farmer cooperatives and savings clubs. Practical implications: The findings suggest that policy strategies aiming to improve access to savings and credit services should educate farmers and strengthen FBOs that could serve as entry points for financial service providers. Such market smart strategies have the potential to improve farmers' access to financial services and reduce rural poverty. Originality/value: Although existing studies have examined farmers' participation in credit markets and credit rationing separately, the unique contribution of this paper is the analysis of participation in microcredit programs as well as the likelihood of farmers being credit rationed in Ghana.